Recent Advances in Liquid Biopsy in Patients With Castration Resistant Prostate Cancer - Di Nunno, Vincenzo; Gatto, Lidia; Santoni, Matteo; Cimadamore, Alessia; Lopez-Beltran, Antonio; Cheng, Liang; Scarpelli, Marina; Montironi, Rodolfo; Massari, Francesco (Frontiers in Oncology, 2018)
Management of localized and advanced prostate cancer benefits from several therapeutic options with a surprising improvement in terms of clinical outcome. The selection of patients more likely to benefit from a specific approach still remains a key issue as well as the early identification of patients with aggressive disease which could benefit from a more aggressive treatment strategy. The lack of reliable bio-marker in castration resistant setting able to monitor response to treatment and early inform about tumor progression is an emerging issue. Accordingly, circulating DNA and circulating tumor cells appears a promising and attractive approach despite to date practical applications of these techniques are few and not validated. The aim of this review of the literature is to explore current knowledge on liquid biopsy in prostate cancer focusing on possible future applications.